DINAMIKA KINERJA KEUANGAN PT GARUDA INDONESIA (PERSERO) TBK PERIODE 2019–2023 - Elvira Nursan; Sri Retnaning Sampurna Ningsih; Ahmad Affandi; Maulidina Alfadilah (Bisnis-Net, 2026)
This study aims to examine the dynamics of the financial performance of PT Garuda Indonesia (Persero) Tbk during the pre-crisis period, the COVID-19 crisis, and the post-crisis recovery phase from 2019 to 2023. A descriptive quantitative approach is employed using financial statement analysis, including vertical analysis, horizontal analysis, and financial ratio analysis covering profitability, liquidity, solvency, operational efficiency, and market ratios. The study utilizes secondary data derived from the company’s audited annual financial statements and official publications of the Indonesia Stock Exchange. The results indicate that prior to the pandemic, the company’s operational performance was relatively stable but exhibited underlying structural vulnerabilities. During the crisis period of 2020–2021, the sharp decline in air travel demand evolved into significant financial distress, as reflected in declining profitability, weakened operating cash flows, increased leverage, and the emergence of negative equity. In the post-crisis period of 2022–2023, financial performance began to recover in line with demand rebound and financial restructuring, although the recovery remained partial and was not yet fully supported by structural cost efficiency. These findings underscore the importance of strengthening cost efficiency and capital structure to enhance the long-term financial resilience of state-owned airlines in the face of external shocks.